2021
DOI: 10.1186/s13075-021-02439-5
|View full text |Cite
|
Sign up to set email alerts
|

Advanced machine learning for predicting individual risk of flares in rheumatoid arthritis patients tapering biologic drugs

Abstract: Background Biological disease-modifying anti-rheumatic drugs (bDMARDs) can be tapered in some rheumatoid arthritis (RA) patients in sustained remission. The purpose of this study was to assess the feasibility of building a model to estimate the individual flare probability in RA patients tapering bDMARDs using machine learning methods. Methods Longitudinal clinical data of RA patients on bDMARDs from a randomized controlled trial of treatment withd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 13 publications
1
14
0
1
Order By: Relevance
“…Two studies have incorporated such dynamic variables to predict RA disease activity over time [ 24 , 25 ]. The study by Norgeot et al [ 24 ] found the Clinical Disease Activity Index (CDAI), CRP/ESR, glucocorticoid use, and other DMARD use to be important predictors.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have incorporated such dynamic variables to predict RA disease activity over time [ 24 , 25 ]. The study by Norgeot et al [ 24 ] found the Clinical Disease Activity Index (CDAI), CRP/ESR, glucocorticoid use, and other DMARD use to be important predictors.…”
Section: Discussionmentioning
confidence: 99%
“…The RETRO clinical trial has previously generated predictive models that were based on clinical parameters and serum studies ( 16 , 17 ). ACPA seropositivity appears to be an important indicator for increased risk of future relapse ( 17 ), while clinical parameters have modest predictive value even when combined with advanced machine learning techniques ( 43 ). It remains unclear if these indicators are clinically applicable and generalizable to a wide range of RA patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Erythrocyte Sedimentation Ratebased Disease Activity Score in 28 joints (DAS28-ESR), C-reactive protein-based Disease Activity Score in 28 joints (DAS28-CRP), Clinical Disease Activity Index (CDAI) score, and the Simplified Disease Activity Index (SDAI, 0-86) were also used to grade the disease [2,5,6,16].…”
Section: Clinical Assessment Of Disease Activitymentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is one of the chronic inflammatory diseases that cause erosive arthritis and consequently functional loss if it is not treated with early effective treatment modalities [ 1 , 2 ]. Remission rates usually depend on several factors belonging to the patients and the medications used for RA.…”
Section: Introductionmentioning
confidence: 99%